Psychiatric and neuropsychiatric sequelae of COVID-19 – A systematic review - Schou, Thor Mertz; Joca, Samia; Wegener, Gregers; Bay-Richter, Cecilie (Brain, behavior, and immunity, 2021)
•66 studies examined psychiatric or neuropsychiatric sequelae following COVID-19.•Fatigue, anxiety/depression, PTSD, cognitive deficits, and sleep disturbances were most commonly reported.•COVID-19 survivors were at risk of psychiatric sequelae but symptoms generally improve over time. It has become evident that coronavirus disease 2019 (COVID-19) has a multi-organ pathology that includes the brain and nervous system. Several studies have also reported acute psychiatric symptoms in COVID-19 patients. An increasing number of studies are suggesting that psychiatric deficits may persist after recovery from the primary infection. In the current systematic review, we provide an overview of the available evidence and supply information on potential risk factors and underlying biological mechanisms behind such psychiatric sequelae. We performed a systematic search for psychiatric sequelae in COVID-19 patients using the databases PubMed and Embase. Included primary studies all contained information on the follow-up period and provided quantitative measures of mental health. The search was performed on June 4th 2021. 1725 unique studies were identified. Of these, 66 met the inclusion criteria and were included. Time to follow-up ranged from immediately after hospital discharge up to 7 months after discharge, and the number of participants spanned 3 to 266,586 participants. Forty studies reported anxiety and/or depression, 20 studies reported symptoms- or diagnoses of post-traumatic stress disorder (PTSD), 27 studies reported cognitive deficits, 32 articles found fatigue at follow-up, and sleep disturbances were found in 23 studies. Highlighted risk factors were disease severity, duration of symptoms, and female sex. One study showed brain abnormalities correlating with cognitive deficits, and several studies reported inflammatory markers to correlate with symptoms. Overall, the results from this review suggest that survivors of COVID-19 are at risk of psychiatric sequelae but that symptoms generally improve over time.